(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Sultan Raev s novel «Zhanjaza» is one of the profound philosophical works in modern Kyrgyz literature. The narrative explores themes of spiritual quest, the meaning of life and death, reincarnation of the soul, and the concept of eternity. By intertwining mythological figures with historical characters, the 4 core philosophical idea of the novel lies in humanity s pursuit of spiritual freedom and immortality.